Le coût de l’électricité au Québec : 1976-1990 - Boyer, Marcel; Martin, Fernand (L'Actualité économique, 1978)
In this paper, the authors develop a model for evaluating the marginal cost of electricity in the Province of Quebec for the period 1976-90. This model requires only available data, namely, the operating cost for the year 1976-77 and the investment plan for the 1976-1985 period. It makes possible the determination of the marginal cost of electricity without having to use a mathematical programming approach for which the required data are not always available.